First record of the anisakid nematode Anisakis nascettii in the Gervais' beaked whale Mesoplodon europaeus from Brazil. Issue 1 (28th October 2014) - Di Azevedo, M.I.N.; Carvalho, V.L.; Iñiguez, A.M.
Abstract: Anisakid nematodes are parasites with an indirect life cycle, involving many hosts, including cetaceans that act as definitive hosts. Identification at species level is crucial for a better understanding of the epidemiology and ecology of these parasites, but an accurate diagnosis based only on morphology is difficult. In Brazil, genetic characterization of anisakids is still rare, with Anisakis typica and A. physeteris being the only two species identified by genetic markers until now. The definitive hosts of A. nascettii are Mesoplodon grayi, M. bowdoini, M. layardii and M. mirus . Geographical locations of A. nascettii include the coasts of New Zealand, South Africa and Europe. In this study, a nematode was collected from a Gervais' beaked whale, Mesoplodon europaeus, stranded in Ceará State, north-east Brazil. Genetic analysis based on 18S rDNA, internal transcribed spacer (ITS) region and mtDNA cox 2 gene revealed 100% identity with Anisakis sp. U94365, 99% with Anisakis sp. (MP-2005 EU718477 A. nascettii ) and 99% with A. nascettii DQ116431, respectively. Phylogenetic analyses of ITS and cox 2 sequences using both neighbour-joining and maximum-likelihood methods provided strong support for a clade with only A. nascettii specimens. This study demonstrated for the first time the identification of A. nascettii in the Brazilian Atlantic Coast, revealing a wider geographical distribution of this parasite worldwide and extending the range of its definitive hosts to a new Mesoplodon species, M. europaeus, the Gervais' beaked whale.